Acute vessel closure salvaged by use of the retrograde approach. (April 2014) - Kotsia, Anna P; Banerjee, Subhash; Brilakis, Emmanouil S
Acute vessel closure is a percutaneous coronary artery complication with potential catastrophic consequences. In this article we report a case where the retrograde approach was used to salvage an acute vessel occlusion during a first obtuse marginal percutaneous coronary artery.